Real-Time Digital Feedback Device and Simulated Newborn Ventilation Quality - Data, Santorino; Nelson, Brett D.; Cedrone, Kevin; Mwebesa, Winifride; Engol, Santa; Nsiimenta, Naome; Olson, Kristian R. (Pediatrics, 2023)
Objectives: Effective bag-valve-mask ventilation is critical for reducing perinatal asphyxia-related abstract neonatal deaths; however, providers often fail to achieve and maintain effective ventilation. The Augmented Infant Resuscitator (AIR) attaches to bag-valve-masks and provides visual feedback on air leaks, blocked airways, harsh breaths, and improper ventilatory rates. We evaluated the effect of this real-time-digital feedback on ventilation quality and the effective determination of airway integrity in a randomized controlled study in Uganda and the United States. Methods: Birth attendants trained in newborn resuscitation were randomized to receive either real-time AIR device feedback (intervention) or no feedback (control) during ventilation exercises. Intervention-arm participants received a 2-minute orientation on interpreting AIR feedback using a single-page iconography chart. All participants were randomly assigned to 3 blinded ventilation scenarios on identical-appearing manikins with airways that were either normal, significantly leaking air, or obstructed. Results: We enrolled 270 birth attendants: 77.8% from Uganda and 22.2% from the United States. Birth attendants receiving AIR feedback achieved effective ventilation 2.0 times faster: intervention mean 13.8s (95% confidence interval 10.6–17.1) versus 27.9s (21.6–34.3) for controls (P < .001). The duration of effective ventilation was 1.5 times longer: intervention mean 72.1s (66.7–77.5) versus 47.9s (41.6–54.2) for controls (P < .001). AIR feedback was associated with significantly more accurate and faster airway condition assessment (intervention mean 43.7s [40.5–47.0] versus 55.6s [51.6–59.6]). Conclusions: Providers receiving real-time-digital AIR device feedback achieved effective ventilation significantly faster, maintained it longer, and determined airway condition faster and more accurately than providers in the control group.
Keywords: Real-Time Digital Feedback Device; Augmented Infant Resuscitator (AIR); Uganda